Utilising electroanatomic mapping during ablation in patients with CHD to reduce radiation exposure - Rahman, Maryam; Moore, Jeremy P.; Papagiannis, John; Smith, Grace; Anderson, Chris; Shannon, Kevin M.; Razminia, Mansour; Tuzcu, Volkan; McNinch, Neil L.; Shauver, Lisa M.; Clark, John M. (Cambridge University Press, 2022)
Background: Patients with CHD can be exposed to high levels of cumulative ionising radiation. Utilisation of electroanatomic mapping during catheter ablation leads to reduced radiation exposure in the general population but has not been well studied in patients with CHD. This study evaluated the radiation sparing benefit of using three-dimensional mapping in patients with CHD. Methods: Data were retrospectively collected from the Catheter Ablation with Reduction or Elimination of Fluoroscopy multi-institutional registry. Patients with CHD were selected. Those with previous ablations, concurrent diagnostic or interventional catheterisation and unknown arrhythmogenic foci were excluded. The control cohort was matched for operating physician, arrhythmia mechanism, arrhythmia location, weight and age. The procedure time, rate of fluoroscopy use, fluoroscopy time, procedural success, complications, and distribution of procedures per year were compared between the two groups. Results: Fifty-six patients with congenital heart disease and 56 matched patients without CHD were included. The mean total procedure time was significantly higher in patients with CHD (212.6 versus 169.5 minutes, p = 0.003). Their median total fluoroscopy time was 4.4 minutes (compared to 1.8 minutes), and their rate of fluoroscopy use was 23% (compared to 13%). The acute success and minor complication rates were similar and no major complications occurred. Conclusions: With the use of electroanatomic mapping during catheter ablation, fluoroscopy use can be reduced in patients with CHD. The majority of patients with CHD received zero fluoroscopy.
Keywords: Arrhythmia; Catheter Ablation; CHD; Radiation; Three-Dimensional Mapping; Zero Fluoroscopy